2015
DOI: 10.14202/vetworld.2015.631-635
|View full text |Cite
|
Sign up to set email alerts
|

Critical sources of bacterial contamination and adoption of standard sanitary protocol during semen collection and processing in Semen Station

Abstract: Aim:The present investigation was conducted to locate the critical sources of bacterial contamination and to evaluate the standard sanitation protocol so as to improve the hygienic conditions during collection, evaluation, and processing of bull semen in the Semen Station.Materials and Methods:The study compared two different hygienic procedures during the collection, evaluation and processing of semen in Central Semen Station, Anjora, Durg. Routinely used materials including artificial vagina (AV) inner liner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Biotic [48,49]. e potential abiotic contaminants could come from laboratory environments such as semen collection, transporting and processing equipment, processing laboratory, glassware, buffers, extender, and straws [50]. Other contaminants are related to semen diluents like egg yolk [14,51], resistant to antibiotics [52], and low efficacy of antimicrobials used in the extender [16,[53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic [48,49]. e potential abiotic contaminants could come from laboratory environments such as semen collection, transporting and processing equipment, processing laboratory, glassware, buffers, extender, and straws [50]. Other contaminants are related to semen diluents like egg yolk [14,51], resistant to antibiotics [52], and low efficacy of antimicrobials used in the extender [16,[53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Other contaminants are related to semen diluents like egg yolk [14,51], resistant to antibiotics [52], and low efficacy of antimicrobials used in the extender [16,[53][54][55]. Nevertheless, bacterial load can be reduced considerably by applying hygienic practices of packaging, handling, sterilization and fumigation protocol [48,50], and preputial washing [56].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial contamination results in a reduction in the pH of the diluents as well as this pH affect the overall quality of sperm cells. Studies have a shown significant reduction in sperm motility and viability in acidic pH during microbial contamination [ 48 ]. Due to low pH, the post-thaw quality of spermatozoa also gets reduced and resulted in poor or compromised conception rates [ 49 , 50 ].…”
Section: Ph Regulatory Mechanisms In Different Animalsmentioning
confidence: 99%
“…Semen collected at Semen Stations inevitably contains ambient microorganisms, up to 2.36 × 104 ± 1943 CFU/mL in fresh semen [57] and 1.00 × 10 ± 90 CFU/mL in frozen semen after thawing [58]. Other authors found 103-106 CFU/mL in five bulls analysed after collection at an insemination centre [59] and 50.38 ± 16.29 CFU/mL in thawed cryopreserved bull semen collected under field conditions [60].…”
Section: Discussionmentioning
confidence: 99%